Causally-Rich Group Play: A Powerful Context for Building Preschoolers’ Vocabulary - Bauer, Jessie Raye; Booth, Amy E.; McGroarty-Torres, Kathleen (Frontiers in Psychology, 2016)
This work explores whether the facilitative effect of causal information on preschoolers’ word learning observed in the laboratory might be relevant to boosting children’s vocabulary in a group-play context. Forty-eight 3- to 4-year-old children learned six novel words for novel tools introduced during a small group-play session. Half of the groups used the tools according to their specified function to construct a fruit salad. The remaining children used the same tools to decorate a castle of blocks. In this way, some children learned about the causal properties of the tools, while others did not. Although children in both conditions comprehended the novel words equally well when tested shortly after the play session, learning in the Causal condition was more robust. Children’s comprehension scores in the Causal condition increased over time (a 7-20 day delay), such that children in this group performed better than children in the Non-Causal condition when tested in a follow-up session. These results demonstrate a striking benefit of causal enrichment to word learning in a context that could feasibly be implemented in preschool classrooms, playgroups, and individual households. Highlighting the causal properties of objects during playtime might offer a powerful approach to building children’s vocabulary, thereby providing a stronger foundation for early literacy and success in school more generally speaking.